Rigorous Phenomenography: A Conceptual Model - Dr. Jennifer M. Straub; Dr. Nancy Maynes (Journal of Studies in Education, 2024)
This paper presents a visual conceptual model for the qualitative research approach referred to as phenomenography. The static and recursive stages of a rigorous phenonemographical approach to research are outlined in detail. Using the example of a research study situated in pre-service teacher education, the authors explain how the fifteen distinct steps of phenomenographic research should be addressed with attention to the sequencing of these steps to support reliability and rigor of the research process and validity and generalizability of the outcome spaces that may result from the use of phenomenography.